2013
DOI: 10.1159/000346670
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Symptom Evaluation in Daily Oncology Practice: A Survey of 150 Patients with Advanced Gastrointestinal Tumours Receiving Palliative Chemotherapy

Abstract: Background: Quality of life (QoL) is frequently investigated as a secondary endpoint in clinical trials but is rarely evaluated in clinical practice. The present survey sought to assess the QoL of patients with advanced gastrointestinal tumours receiving palliative chemotherapy. Furthermore, we wanted to compare the results of subscales of the generic EORTC QLQ-C30 (European Organization for Research and Treatment of Cancer, Quality of Life Questionnaire, version 3.0) using assessment tools with an emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This is an expected result since the pain group has greater pain. Previous studies demonstrated a significant correlation between pain and low quality of life score in terminal cancer patients39,40) and a consistent result is expected when the sample size increases.…”
Section: Discussionsupporting
confidence: 75%
“…This is an expected result since the pain group has greater pain. Previous studies demonstrated a significant correlation between pain and low quality of life score in terminal cancer patients39,40) and a consistent result is expected when the sample size increases.…”
Section: Discussionsupporting
confidence: 75%